Towards a Sustainable Model of Higher Education in the Araucanía Region, Chile. Issue 1 (May 2020) - Navarrete, C; Saldías, G; Carbonetti, M; Fierro, J M; Sandoval, D
Abstract: The aim of this article is to propose a critical reflection of the state of teaching sustainability in higher education in Chile. The goal is to broaden the concept of sustainability so as to understand its implication in learning civic and community values, as well as in implementing innovative teaching methodologies linked to the promotion of sustainable values connected to the United Nations' Sustainable Development Goals. In this article, the application of a teaching methodology called Pre-Texts, from Harvard University, is explored in a sociocultural context of Chilean higher education, specifically at the Universidad de La Frontera in Chile's 9 th Region. Evidence is sought about how this methodology is relevant and effective in the teaching of two key pedagogical principles related to sustainability: the importance of community recognition and the collective work and implementation of artistic practices to promote discussion of sustainable principles based on preservation and recycling. Finally, a conclusion will be pursued around the need to implement these and similar teaching practices in higher education to promote greater awareness of the fundamental principles of Sustainable Development.